Strategy to Increase B2B Readiness in PT Telkom Indonesia Regional 3 During Organizational Transformation - Qinthara Silmi Faizal; Achmad Ghazali (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
PT Telkom Indonesia implemented a strategic restructuring plan to boost its competitive advantage and reinforce its position in the Indonesian telecommunication industry. The first strategy is fixed mobile convergence (FMC), which changed all Telkom Regional target markets and business models from B2C to B2B. Telkom Regional 3, which served customers in the West Java region, was designated by management as a pilot for Telkom Regional in its transformation to B2B. During the organizational transformation process, B2B readiness survey was conducted to see whether employees in each region are ready for transformation. The result showed that Telkom Regional 3 has the lowest score in B2B readiness compared to the average score and the other six regions. The area that needs to be improved by Telkom Regional 3 is related to capability subject matter expert (SME), territory leadership, and partnership policy model. The framework used in this research is the KPMG six layer target operating model. The data was collected by interview to validate the business issue and gain more comprehensive insight based on KPMG six layer target operating model variables. The result showed that the first issue occurs because of the gap between subject matter expert (SME) expectations and reality regarding B2B business. Also, no figure leader B2B can give an example of an ideal B2B business. The second issue occurred because there is a need for a shift in mindset from B2C to B2B for teams in the territory, and the last issue arose because of rigid partnership policy. This research is expected to provide an overview of the causes of the low B2B readiness score in Telkom Regional 3, along with suggestions for further improvement.